Aktivitas Antimikroba Ekstrak Etanol Biji Pinang Muda (Areca catechu) - Sega Ade Lilyawati; Nurul Fitriani; Fajar Prasetya (Proceeding of Mulawarman Pharmaceuticals Conferences, 2019)
Thrush is an oral disease caused by bacterial and fungal infections. Treatment for this disease can be done by administering drugs that contain antimicrobial compounds. This study aims to test the ethanol extract of young areca nut against bacteria and fungi that cause Oral thrush. Young betel nut extract is obtained through maceration process using 96% ethanol. Then the activity of the Streptococcus sanguis bacteria and Candida albican fungus was tested. This test used the well method which was carried out on 5 variations of the concentration of young areca nut extract (2.5%; 5%; 7.5%; 10% and 15%) with one negative control (Na CMC). The results of the antimicrobial activity of young areca nut extract showed that young areca nut extract can inhibit Streptococcus sanguis bacteria with inhibition value are (9,961; 11,319; 13,390; 14,184; 14,704 mm) and Candida albican fungus are (7,482; 10,923; 14,695; 15,742; 17,325 mm) on 5 variations of the concentration.